2021
DOI: 10.3389/fpsyg.2021.713081
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice and Ethnic Bullying Among Children: The Role of Moral Disengagement and Student-Teacher Relationship

Abstract: The identification of factors associated with ethnic bullying within multiethnic schools is a timely social issue. Up to now, ethnic prejudice has been found to facilitate aggression triggered by schoolmates’ cultural background. Yet, there is still a dearth of research about the mechanisms underlying this relation among children. In order to fill this gap, by adopting a social-cognitive developmental perspective on prejudice and morality, this paper investigated the mediating role of moral disengagement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
6
0
2
Order By: Relevance
“…Morally disengaged students are seen as more likely to engage in bullying. Such disengagement is likely to be influenced by group membership and the social norms they share, as well as by personal prejudice (Iannello et al, 2021).…”
Section: Intenɵon To Bullymentioning
confidence: 99%
“…Morally disengaged students are seen as more likely to engage in bullying. Such disengagement is likely to be influenced by group membership and the social norms they share, as well as by personal prejudice (Iannello et al, 2021).…”
Section: Intenɵon To Bullymentioning
confidence: 99%
“…By using disengagement processes, the individual redefines harmful conduct as honorable. In the context of racist/ethnic bullying in schools, moral disengagement mediates the relation between ethnic prejudice (attitudes) and ethnic harassment and bullying (behavior) by making the harassment and the bullying appear legitimate (Iannello et al, 2021). At the adult level, there is substantial empirical evidence supporting the link between moral disengagement and support for political extremism (Nivette et al, 2017).…”
Section: Convergences In the Conceptual Constituents Of The Prejudice...mentioning
confidence: 99%
“…The author notes that such prejudice may stem from collective memories of Britain’s relation to Germany during the First and Second World Wars, and negative unsympathetic images of the German ‘enemy’ in textbooks, television programs, and even in children’s comic books (Rutland, 1999: 66). Today, in the 21st century, schools, which are supposed to be a safe haven for children’s optimal development, are still challenged by the mushrooming of racist and ethnocentric movements against minority students (Iannello et al, 2021; Sapouna et al, 2022; Xu et al, 2020).…”
Section: Determinants Of the Prejudiced Mindsetmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one Swedish study showed that students demonstrating higher moral disengagement in conjunction with poorer student-teacher relationship quality were more prone to reinforce in bullying situations ( Sjögren et al, 2021b ). Another study on ethnic bullying in Italy showed that closeness to teachers might restrain morally disengaged children from bullying ( Iannello et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%